Cyclic Guanosine 3′,5′-Monophosphate in the Dimorphic Fungus Mucor racemosus - Orlowski, Michael (1976)
The dimorphic fungus Mucor racemosus was found to contain the cyclic nucleotide guanosine 3′,5′-monophosphate (cGMP). Approximately equivalent amounts of the compound were found in ungerminated spores, yeastlike cells, and mycelia. Germinating spores contained severalfold higher amounts of cGMP than the other cell forms. cGMP levels did not change significantly during the morphogenetic conversion of yeast to mycelia. Added exogenous cGMP or the dibutyryl derivative did not influence cell morphology in any way and did not alter the effect that cyclic adenosine 3′,5′-monophosphate has upon cell morphology.